(untitled) (Research, Society and Development, 2022)
This work presents an economical, technical, and environmentally correct solution for the disposal of long neck bottles (which cannot be bottled more than once), by replacing fine aggregates (sand) with residue of ground glass from long neck bottles in the production of reactive powder concrete (RCP). Using a reference formulation for RCP containing natural sand, this raw material was replaced in 12.5, 25, 50, 75 and 100 wt.% by glass residues, evaluating the physical and mechanical properties in the specimens at the ages of 7, 14, and 28 days. The ground glass was characterized by X-ray Fluorescence and DSC tests, indicating that it is a typical sodo-calcium glass, with a glass transition temperature equals to 560C. Grain size distribution and optical microscopy assays of natural sand and ground glass indicated that the comminution let to the acquisition of glass with granulometry similar to that of natural sand, but with very different geometries and roughness. The replacement of natural sand by 100% of ground glass presented the best results of mechanical properties, reaching 85% of the mechanical strength value of the reference composition, with about 96MPa; this composition also presented the lowest water absorption value (3.94%) and the lowest void index (9.33%) among all compositions. The results indicated that the replacement of sand by powder from long neck bottles is potentially feasible, promoting an environmentally correct destination for this residue in the construction sector, bringing a reduction in environmental impact, and generating concrete within the technical standards required by the norm.